THE ABILITY TO CORRECT WRITING ERRORS IN ADDITIONAL WORD AND PARTICLES IN DISCUSSION IN JUNIOR HIGH SCHOOLS - Siti Mariati; Ika Mustika (Jurnal Scientia, 2020)
This study aims to determine the ability to correct affix word and particle writing errors in students' discourse which is obtained by correcting the affixed word and particle writing errors in the discourse. Writing affixed words is limited to writing di- and ke- prefixes, while particle writing is limited to writing per and pun. This study uses a descriptive method because it aims to describe the ability of students to correct errors in writing affix words and particles in discourse by junior high school students. The research sample was 24 junior high school students who were taken randomly from 246 students. To obtain data on the ability to correct writing errors with affix words and particles, it can be seen from the accuracy of writing affix words and particles obtained from the research instrument in the form of a discourse test in which the writing in-, ke-, and also in it is writing that is not following spelling. The results showed that the overall percentage of correcting the writing error of affix words reached 77.86%. For the aspect of correcting the writing error of the prefix, the percentage was 79.76%, while for the accuracy of correcting the writing error of the prefix, the percentage was 64.58%.